REPORT ON THE RESISTANCE TO INSULIN AND THE BENEFITS OF INTENSE EXERCISE IN DIABETES TYPE 2 - De Sousa, Ricardo Augusto Leoni (2014)
Diabetes mellitus type 2 (DM2) comprises more than 95% of diabetes cases worldwide. It main characteristic is its resistance to insulin which causes the development of hyperglycemia and hyperinsulinemia. Current study analyzes through a revision of the literature the benefits of resisted exercise in the resistance to insulin and its understanding. The key point in DM2 metabolism and its main causes are the protein kinase B (AKT) and Phosphatidylinositol-3-kinase (PI3-K). Resistance to insulin is associated with defects in the activation of receptors of insulin 1 and 2 and/or low activation of PI3-K and/or the slight displacement of GLUT-4, a transporter of glucose. Its intracellular movement depends on AKT signalization. High intensity RE is capable of promoting a greater phosphorylation of insulin receptors and/or increasing the activity of PI3-K and/or raising the translocation of the main glucose vehicle during physical activity and GLUT-4, by a greater activation of AKT. Intense RE strives against insulin resistance and favors a greater and better functioning of the PI3-K pathway.